2006
DOI: 10.1017/s0265021506000305
|View full text |Cite
|
Sign up to set email alerts
|

The effect of adding two target-controlled concentrations (1–3 ng mL−1) of remifentanil on MACBAR of desflurane*

Abstract: A target-controlled concentration of 1 ng mL(-1) remifentanil results in a 57% decrease in the MAC(BAR) of desflurane combined with 60% nitrous oxide. Increasing the target concentration of remifentanil to 3 ng mL(-1) produces a further 26% decrease in the MAC(BAR) values of desflurane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 27 publications
(63 reference statements)
0
18
0
Order By: Relevance
“…Its elimination half-life is 3-5 min (Hughes et al, 1992;Kapila et al, 1995;Soltesz et al, 2001). It has been reported (Soltesz et al, 2001;Albertin et al, 2005Albertin et al, , 2006 that remifentanil, combined with other anesthetics at a target concentration of 1-3 ng/mL in the plasma, can inhibit the sympathetic response in 50% of patients when the skin is incised. A target concentration of 4 ng/mL remifentanil is required for intubation, and the target concentration is maintained at 2-5 ng/mL during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Its elimination half-life is 3-5 min (Hughes et al, 1992;Kapila et al, 1995;Soltesz et al, 2001). It has been reported (Soltesz et al, 2001;Albertin et al, 2005Albertin et al, , 2006 that remifentanil, combined with other anesthetics at a target concentration of 1-3 ng/mL in the plasma, can inhibit the sympathetic response in 50% of patients when the skin is incised. A target concentration of 4 ng/mL remifentanil is required for intubation, and the target concentration is maintained at 2-5 ng/mL during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Daniel et al reported that fentanyl decreased the MAC BAR (blockade of autonomic response) ETC of desflurane when used with N 2 O [8]. Albertin et al reported on remifentanil used in combination with desflurane and 60% N 2 O and infused remifentanil at target concentrations of 1 ng/ml and 3 ng/ml using TCI at 5 min after the first surgical incision and they found that the MAC BAR ETC was decreased to 2.7% and 2.0%, respectively; this showed significant reducing effects of about 37% and 45%, respectively [6]. When performing anesthesia induction, laryngeal manipulation and endotracheal intubation can cause severe hemodynamic changes, To prevent these changes, at least a 1.5 MAC anesthetic concentration is required [9], and depending on different stimuli, the systolic blood pressure and HR can greatly change [10].…”
Section: Discussionmentioning
confidence: 99%
“…This is probably related to the very rapid onset of effect the drug (Nieuwenhuijs et al 2003;Habib et al 2002;Dimitriou et al 2006;Lecomte et al 2006;Bilgin et al 2006;Chanavaz et al 2005;Locala et al 2005;Pleym et al 2004;Ouattara et al 2004;Godet et al 2004;Heijmans et al 2004;Joo et al 2004;Unlugenc et al 2003;Jellish et al 2003;Manyam et al 2006;Albertin et al 2006;Mustola et al 2005;Albertin et al 2004;Bouillon et al 2004;Kern et al 2004;Drover et al 2004;Mertens et al 2003;Milne et al 2003;Fechner et al 2003;Criado and Gomez e Segura 2003;Bothtner et al 2002).…”
Section: Central Nervous Systemmentioning
confidence: 99%
“…Without opioid, the hypnotic concentration required for loss of consciousness is lower than the one to prevent response to noxious stimulations (around 1/3 MAC). It is moderately reduced by low-dose opioids: for example, propofol concentration for loss of consciousness is reduced by 25% in the presence of remifentanil 6 ng/ml (Nieuwenhuijs et al 2003;Manyam et al 2006;Albertin et al 2006;Mustola et al 2005;Albertin et al 2004;Bouillon et al 2004;Kern et al 2004;Drover et al 2004;Mertens et al 2003;Milne et al 2003;Fechner et al 2003;Criado and Gomez e Segura 2003;Bothtner et al 2002). Consequently, at high opioid concentrations the hypnotic needs for loss of consciousness may be higher than those to prevent response to noxious stimuli, and a patient might show no response to surgery and be completely awake, especially if he cannot move to signal his awareness because of neuromuscular blockade.…”
Section: Interactions With Hypnoticsmentioning
confidence: 99%